KERAGAMAN KONSUMSI PANGAN PADA BALITA STUNTING DI WILAYAH PEDESAAN DAN PERKOTAAN KABUPATEN PROBOLINGGO [Dietary Diversity among Stunting Toddlers in Rural and Urban Areas of Probolinggo Regency] - Dhita Kusuma Astuti; Sri Sumarmi (Universitas Airlangga, 2020)
One of the main nutritional problems faced by developing countries is stunting. Probolinggo Regency is one of the government priority to overcome stunting problem in Indonesia with prevalence of stunting up to 49.43%. Rural area have higher prevalence of stunting compare to urban area. Dietary diversity associate with stunting. This study aimed to analyze the diff erences of dietary diversity among stunting toddlers in rural and urban area of Probolinggo Regency. A cross sectional study design was used with total sample as much as 44 stunting toddlers aged 12-59 months in rural and 44 stunting toddlers with the same age in urban area. Sample was determined by multistage cluster sampling. Data were collected using IDDS instrument and rated twice with minimum consumption of 10 grams. Data were analyzed using T-test. Result showed that there were no signifi cant diff erences on dietary diversity (p=0.106) among stunting toddlers in rural and urban area. Dietary diversity among stunting toddlers in urban area are slightly better than rural area. Based on 9 food groups, stunting toddlers both in rural and urban area were not consuming organ meat. It was concluded that dietary diversity among stunting toddlers in rural area was not diff erent from dietary diversity among stunting toddlers in urban areas. Mother should give more diverse food to their children, especially fruits, vegetables, nuts and seeds, milk and milk products, and introduce organ meat such as chicken liver.